Prediction of long-term survival in patients with metastatic gastrointestinal stromal tumor: analysis of a large, single-institution cohort. (3rd October 2017) - Hompland, Ivar; Bruland, Øyvind Sverre; Hølmebakk, Toto; Poulsen, Jan Peter; Stoldt, Stephan; Hall, Kirsten Sundby; Boye, Kjetil
Abstract: Background: A subset of patients with metastatic GIST become long-term survivors, and a more precise prediction of outcome could improve clinical decision-making. Material and methods: One-hundred and thirty-three patients diagnosed with metastatic GIST from 1995 to 2013 were identified from the sarcoma database at Oslo University Hospital. Clinical data prospectively registered in the database were supplemented with retrospective review of medical records. Factors associated with survival were analyzed using Kaplan–Meier curves, log-rank test, univariate and multivariate Cox regression analyses. Results: One-hundred and fifteen patients with metastatic GIST were included in the final study cohort. Median overall survival (OS) was 6.9 years (95% CI 5.6–8.3). Factors associated with long-term survival in univariate analysis were good baseline performance status (ECOG ≤1; p  < .001), young age ( p  = .022), oligometastatic disease (OMD) (≤3 metastases; p  < .001), maximum tumor diameter <5 cm ( p  < .001), surgery for metastatic disease ( p  = .005), surgery of the primary tumor ( p  < .001), normal baseline hemoglobin level ( p  = .05), normal baseline albumin level ( p  = .001) and normal baseline neutrophil count ( p  = .03). On multivariate analysis, good performance status, small tumor diameter and, OMD were the factors associated with long-term survival. Five and 10-year OS for patients with OMD were 89% and 71%, respectively, compared to 38% and 20% for patients with polymetastatic disease ( p  < .001). Conclusions: In this single-institution cohort of patients, OMD was as a strong prognostic factor in patients with metastatic GIST. Patients with OMD had an outcome similar to patients with high-risk localized disease, and should be regarded as a separate category among patients with metastatic GIST.